Faktor Eksposi terhadap Kualitas Citra Radiografi dan Dosis Pasien Menggunakan Parameter Penilaian Signal to Noise Ratio (SNR) pada Pemeriksaan Thorax Posteroanterior dengan Menggunakan Pesawat Computed Radiografi - Surdiyah Asriningrum; Khaerul Ansory; Putra Tri Hasan (Jurnal Imejing Diagnostik (JImeD), 2021)
Background: The research was analyzing digital image quality and estimation dose patient by using  Signal to Noise Ratio (SNR) on Computed Radiography. SNR can be used for analyzing digital image spatial resolution and estimation dose accurately. The aims of this study to determine the influence of exposure factors on image quality and estimation dose patient.Methods: This type of research is a quantitative method with an experimental study. Direct experiments in August 2020 assessment with a sample of 9 adults posteroanterior chest photo with the average age of 20-50 years old with an average body weight of 50-69 kilograms. Results: The measurement results showed that the digital images will be analyzed by SNR, so it can be determined the optimum exposed factor of the highest SNR value and dose radiation. From the analysis, the highest SNR value at 121 kV, current 1 mAs, the lower dose radiation at 121 kV, current 0,9 mAs.Conclusions: There was an influence variation of an exposed factor on the quality of the image and dose to the patient.